Prevajanje rasističnega diskurza o temnopoltih v slovenščino - Trupej, Janko (Primerjalna književnost, 2014)
This article discusses strategies for translating explicitly racist discourse about black people and racist terms for black people into Slovenian. Thirty-five translations are analysed in order to determine the general characteristics of translating racist discourse about black people over the course of Slovenian history.
Keywords: Beecher-Stowe, Harriet, 1811-1896; Twain, Mark, 1835-1910; Mitchell, Margaret, 1900-1949; Steinbeck, John, 1902-1968; jezik in ideologija; American literature; ameriška književnost; prevajanje; translation; prevodi v slovenščino; temnopolti; rasizem